Pengaruh suhu dan tempat penyimpanan terhadap kadar air dan mutu organoleptik biskuit subtitusi tepung belut (Monopterus albus zuieuw) - Nia Budhi Astuti; Maxianus K Raya; Endah Sri Rahayu (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Biscuits with eel flour substitution contained high energy and protein. Food spoilage during storage is caused by water absorption from food storage. This study examines the effect of storage on the water content of biscuits and organoleptic quality. This research was a quasi-experiment conducted by laboratory analysis of the moisture content of biscuits with the addition of eel flour (Monoptherus albus zuieuw). The experiment was conducted at Jayapura Health Polytechnic Laboratory, consisting of 3 formulas (10, 20 and 30 grams) of eel flour substitution. They were packaged using PP plastic and glass jars. The observations were conducted for seven days at temperatures of -18°C and 45°C. Organoleptic test using 17 somewhat trained panellists. Analysis using Independent T-Test. The results showed that biscuits stored at -18°C experienced an increase in water content on the seventh day. Biscuits stored in plastic packaging have a higher water content than glass jars. There was no significant difference in the water content of biscuits stored in jars and plastics (p=0,631). Organoleptic analysis showed that on the sixth day, there was a change in the preference for taste and texture stored in plastic at temperatures of 45°C. In conclusion, there was no significant difference in the moisture content of the biscuits stored in glass or plastic jars. However, there was a decrease in preference on the sixth day of plastic packaging.